2020
DOI: 10.1101/2020.05.13.093773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PHERI - Phage Host Exploration pipeline

Abstract: Antibiotic resistance is becoming a common problem in health care, veterinary medicine, agriculture or food industry. Multi-resistant bacterial strains occur in all regions of the world. One of the possible future solutions is the use of bacteriophages in therapy.Bacteriophages are the most abundant form of life in the biosphere, so it is highly likely that we can purify a specific phage against each target bacterium. A standard identification and consistent characterization of individual bacteriophages includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“… Putative host genera of the 40 cluster P bacteriophages included in this study ( Supplementary Table 1 ) as predicted by PHERI ( Baláž et al 2020 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Putative host genera of the 40 cluster P bacteriophages included in this study ( Supplementary Table 1 ) as predicted by PHERI ( Baláž et al 2020 ). …”
Section: Resultsmentioning
confidence: 99%
“…Following the best practices suggested by Versoza and Pfeifer (2022) , both exploratory and confirmatory methods were used to computationally predict host ranges for 40 closely related cluster P mycobacteriophages ( Supplementary Table 1 ). First, the exploratory tool PHERI v.0.2 ( Baláž et al 2020 ) was used to predict bacterial host genera. Among the currently available exploratory host range prediction tools, PHERI was the most user-friendly and well-documented, making it ideally suited for course-based undergraduate research experiences.…”
Section: Methodsmentioning
confidence: 99%
“…The use of phages could also enable to combat current unculturable bacteria, on the condition that they can easily be identified through genomic approach. It has been suggested that machine learning approaches can be utilized to either identify, or generate through synthetic genomics, based on the genomic information provided on the bacterial target ( Leite et al, 2018 ; Martorell-Marugán et al, 2019 ; Baláž et al, 2020 ; Pirnay, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…BacteriophageHostPrediction [41] uses more than 200 features-ranging from genomic sequences (such as nucleotide and codon frequencies and GC-content), to protein sequences (such as amino acid frequency), to protein secondary structure (such as α-helix and β-sheet frequencies), and to physicochemical properties (such as molecular weight and isoelectric point)-to represent receptor-binding proteins which play a crucial role in determining host specificity by recognizing receptors on the surface of the bacterial host [47]. At a higher level of sequence representation, PHERI [48] infers bacterial hosts from bacteriophage sequences through annotated protein sequence clusters.…”
Section: Machine-learning Methodsmentioning
confidence: 99%